Implementation of Traditional Medicine Remedies During The COVID-19 Pandemic as Health Improvement and Empowerment of Indonesian Women - Dhigna Luthfiyani Citra Pradana (Sekolah Tinggi Manajemen IPMI, 2021)
The COVID-19 pandemic is still a polemic of life in the world. WHO explains that there are still several countries showing an increase in COVID-19 incident.There are still active case of COVID-19 in Indonesia, which is why Indonesian people should remain vigilant, follow the instruction of the Indonesian Ministry of Health, and do 5M. In addition, the Ministry of Health in Indonesia also recommends using traditional medicine to maintain health, provide adequate nutrition and help overcome health problems. Muslim women groups from various regions in Indonesia can be suitable subjects of community service to assist the government in overcoming the COVID-19 pandemic, one of which is through education about COVID-19 and traditional medicine used during the COVID-19 pandemic. The method used in this community service is through educational webinars and measurement of understanding using an electronic questionnaire. After the educational webinar, the team collected the participant's activity in implementing traditional medicine during the COVID-19 pandemic. The results of this community service activity increased the knowledge of the community service participants to 85.83%. The participants also implemented traditional medicine by sending photos of the activities of the community service participants. This community service activity aims to overcome the problem of information gaps and increase the knowledge of Muslim women groups from various regions in Indonesia to improve and maintain the quality of life and health during the COVID-19 pandemic. Participants in this activity look active and enthusiastic during community service activities.